Wybrane problemy związane z kosztami w logistyce - Skiba, Sławomir (Main Problems of Logistics Costs, 2008)
It is common knowledge that one of the most important tasks of logistics is to minimalize the cost of the flow of goods. Problems involved with logistics costs issue have not been deeply recognized and discussed yet. That is a problem that every manager of logistics has to deal with. This article presents the main problems of logistics' costs, such as: terminology of logistics' costs, logistics' costs account, the scope of analysis of logistics' costs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 124-131